The Effect of Clone Template Parameters on the Spreading Speeds in CNNs (Journal of Nonlinear Modeling and Analysis, 2024)
The aim of this paper is to investigate the effect of clone templateparameters on the spreading speeds in cellular neural networks(CNNs). According to the property analysis of spreading speeds of monotone semiflowsdeveloped by Yu and Zhang [European Journal of Applied Mathematics, 31(2020), 369-384], we investigate the sign of spreading speeds, continuity andlimit cases with no propagation phenomena for CNNs with general outputfunctions where each cell interacts with its 2-neighborhood cell.
Keywords: Sign of spreading speeds; continuity; CNNs.